Teaching Speaking Through Question Game at SMP Dharma Karya Beringin - Armita Sari; Ahmad Laut Hasibuan (Keguruan, 2022)
Games have the potential to be one of the most useful methods of teaching speaking skills, but early observations made about the use of games in class indicate that the game being applied is not suitable for the class. One of the problems observed is that the games used require a lot of time to prepare and only allow a small number of students to talk. This study aims to improve the process of using games to t each speaking by conducting participatory classroom action research in one of the schools in SMP  DHARMA KARYA BERINGIN. The research process follows the steps: Planning, Implementation, Observation, and Reflection. There are two sets of instruments to be used in this study, a list of observations researcher and teacher questionnaires. T he st udents are gi ven a pre-test and post -test to de ter mine the increase in the skills of the students. The results showed that the game ‘Question Game” fits the needs of the class and meets the criteria of ethical speaking game theories after being given several modifications. T-test results on student scores indicate that the improvement made is significant in each cycle. Every aspect of students’ speaking skills also makes a significant improvement with t ob t crit.